PENGHILANGAN SWELL NOISE DAN LINIER NOISE PADA DATA SEISMIK 2D MARINE HIGH RESOLUTION PADA LINTASAN “AF” MENGGUNAKAN METODE SWNA, F-K FILTER DAN TAU-P TRANSFORM - Achmad Subari; Syamsurijal Rasimeng; Nando Liven Konstanta (Engineering Faculty Universitas Lampung, 2018)
Research have been done about noise removal caused by environment (swell noise) and linear noise on high frequency 2D seismic data on line “AF” using swell noise attenuation (SWNA) method, f-k filter and tau-p transformation. Based on obtained result, swell noise succeed removed from data using velocity limited filter that is 1000 m/s on frequency 25 Hz applied to swell noise attenuation process. Applied SWNA data, then created input f-k filter process. In f-k filter process, used polygon design having a minimum frequency limit around 5 Hz maximum high frequency around 450 Hz. The results f-k filter giving a good output with linear noise removal to time 1500 ms. F-k filter output obtained, then processed again using tau-p transformation method. Application of tau-p transformation transformed data into (τ-p) domain. Transformed data on (τ-p) domain, linear noise made on moveout 600 ms. Then the data muted using surgical mute. Based on obtained result, tau-p result can removing linear noise on data. Linear noise removed dominating on time 1500 ms-2500 ms. That matter caused by linear noise on time 0-1500 ms succeed removed using previous process. After the method succesfully applied , data processing continued doing the stack and migration process. Applied migration is postack kirchoff time migration, migration do with migration angel around 300 and aperture around 600 m.